Современное состояние и проблемы кредитования в иностранной валюте в Украине - Макуха, М.С. (Культура народов Причерноморья, 2013)
Статья содержит оценку современного состояния валютного кредитования в Украине и акцентирует внимание на проблемах, связанных с проведением банками кредитных операций в иностранной валюте. Проведен анализ статистической информации Национального банка Украины (данных финансовой отчетности банков, основных показателей деятельности банков, денежно- кредитной статистики), представлен обзор действующих законодательных ограничений по проведению кредитных операций в иностранной валюте, выявлены последствия долларизации кредитных операций и проблемы валютного кредитования в Украине. У статті подана оцінка сучасного стану валютного кредитування в Україні, увагу акцентовано на проблемах, пов'язаних з проведенням банками кредитних операцій в іноземній валюті. Проаналізовано статистичну інформацію Національного банку України (дані фінансової звітності банків, основні показники діяльності банків, грошово-кредитної статистики), представлено огляд чинних законодавчих обмежень щодо проведення кредитних операцій в іноземній валюті, виявлено наслідки доларизації кредитних операцій та проблеми валютного кредитування в Україні. The banking system of Ukraine is characterized by active disposal of foreign currency in deposit and credit operations within the last 10 years. Despite the fact that few currency loans have been granted since 2009, the problem of quality of already generated currency loan portfolios of commercial banks remains crucial. A lot of scientific works are devoted to present condition of bank lending. A special priority in scientific publications is given to the analysis of past-due and repackaged debt of commercial banks. The characteristics and effects of currency substitution of bank assets and liabilities are examined. Due to the fact that specifically dollarized assets constitute a considerable part of bank loan portfolio, including problem debt, there is a demand for additional studies devoted to the reasons and effects of currency substitution of bank assets. The research contains the evaluation of present-day condition of currency crediting in Ukraine; special attention is paid to problems of foreign currency lending operations in banks. The analysis of statistical information of the National Bank of Ukraine was conducted (financial statements, key performance indicators, banking and monetary statistics) concerning the matter in question; the survey of applicable legal restrictions concerning foreign currency lending operations is given; the effects of dollarization of lending operations and problems of foreign currency lending are identified.